Description of length, height, and mandibular gonial angle of Kennedy classification class I, II, III, and IV patients - Z. Paramitha, Andi Irmaya; Sarifah, Norlaila; Wibowo, Diana; Sukmana, Bayu Indra; Azizah, Aulia (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This study aimed to describe the length, height, and mandibular gonial angle of Kennedy classification class I, II, III, and IV patients using panoramic radiographs at Ulin Regional Hospital and GHA Oral and Dental Hospital Banjarmasin. Materials and Methods: This study was descriptive with a cross-sectional design. Sampling used the purposive sampling technique. The research sample was an archive of digital panoramic radiographs of Ulin Regional Hospital and GHA Oral and Dental Hospital Banjarmasin patients aged 30-70 with Kennedy classification, recorded in the Radiology Installation from January 2018 to January 2024. Results: The results from 108 samples of Kennedy classification patients showed that the smallest length of the mandible on the left and right sides is in class I Kennedy. The measurement of mandibular height at points II-R is the smallest in class IV, and the smallest at III-L is in class II. At point II-R, the smallest mean is in class IV, and the smallest at II-L is in class I. The largest measurement of the gonial angle on the left and right sides is in class IV. Conclusion: The mandibular length most likely to cause the temporomandibular disorder is Kennedy class I on the left side in 18 samples (17%). The height and gonial angle of the mandible that most likely causes temporomandibular disorder are on the right side for height and the left side for gonial angle in Kennedy class IV as many as 18 samples (17%).